2017
DOI: 10.1177/1363461517746315
|View full text |Cite
|
Sign up to set email alerts
|

“If I speak English, what am I? I am full man, me”: Emotional impact and barriers for refugees and asylum seekers learning English

Abstract: Lack of proficiency in the language of the host country predicts distress among refugees, but many refugees and asylum seekers in the United Kingdom have less than functional English. This study examined how learning English affected refugees' and asylum seekers' lives, particularly their emotional wellbeing, to explore what factors, particularly psychological ones, facilitated or impeded their learning English. We recruited 16 refugees and asylum seekers from an inner-city National Health Service trauma servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
(130 reference statements)
2
11
0
Order By: Relevance
“…Worryingly, timely access to medical, social or legal support is prohibited by these communication barriers. This echoes previous data that language safeguards asylum seeker access to essential services and support networks (Salvo and Williams, 2017), and that asylum seekers face significant barriers to developing language proficiency whilst in reception centres (Caritas International, 2014). Related evidence from a meta-analysis has shown that where interpreters or translators are not available, the ability to articulate the singularities of different refugee groups and the understanding of their specific difficulties is hampered (Galina et al , 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Worryingly, timely access to medical, social or legal support is prohibited by these communication barriers. This echoes previous data that language safeguards asylum seeker access to essential services and support networks (Salvo and Williams, 2017), and that asylum seekers face significant barriers to developing language proficiency whilst in reception centres (Caritas International, 2014). Related evidence from a meta-analysis has shown that where interpreters or translators are not available, the ability to articulate the singularities of different refugee groups and the understanding of their specific difficulties is hampered (Galina et al , 2017).…”
Section: Discussionsupporting
confidence: 87%
“…This can be seen as the implementation of an approach understood as “total institutions” [1], whereby individual personhood is eroded through varying degrees of communal life. Elsewhere, there have been increasing calls for the consultation and involvement of asylum seekers in the design and adaptation of support services (Majumder et al , 2015) and the policies that concern them (Salvo and Williams, 2017). Whilst one of Fedasil’s founding principles is “guidance of clients,” with the provision of effective and quality support to encourage autonomy and responsibility (Posselt et al , 2018), our findings show that in an absence of sufficient resourcing and flexible bureaucracy there are considerable challenges for staff to foster an environment conducive for individual agency and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the co-researchers also found help with learning English in these charities and felt that this was essential to their sense of progress and integration. This is consistent with research into the importance of third-sector support (Spring et al, 2019) and language acquisition to integration (Salvo and Williams, 2017) and of their role as a protective factor for mental health by distracting from rumination and increasing a sense of self-determination (Labys et al, 2017).…”
Section: Finding Strength Through Connectionsupporting
confidence: 87%
“…The study ends by examining the impact on teacher-student cooperation of many educational programs. Salvo & de C Williams (2017), "What am I about the opportunity I have to speak in English? I am the whole man; I'm full man ": Emotional effects and obstacles for outcasts and refugees learning English.…”
Section: Discussionmentioning
confidence: 99%